1984
DOI: 10.1136/bjsm.18.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Maximum oxygen uptake utilising different treadmill protocols.

Abstract: The study compared five treadmill protocols (four utilising a motorised, and one a non-motorised, treadmill) on maximum oxygen uptake. The five male and five female subjects, all actively engaged in training, were assigned the tests in random order. Statistical analysis revealed no significant differences between the five protocols for maximal oxygen uptake, maximum ventilation, maximum heart rate and blood lactate inflection point, relative to maximal oxygen uptake. Significant differences were observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…As _ V O 2max was higher when using both the Costill/Fox and A Ê strand protocols than the Bruce protocol, our results supported this hypothesis. Indeed, the Costill/Fox protocol produced a test duration of approximately 11 min, which is similar to what has been recommended (Davis et al 1984;McConnell 1988). On the other hand, we found a signi®cantly lower _ V O 2max when following the Bruce protocol.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As _ V O 2max was higher when using both the Costill/Fox and A Ê strand protocols than the Bruce protocol, our results supported this hypothesis. Indeed, the Costill/Fox protocol produced a test duration of approximately 11 min, which is similar to what has been recommended (Davis et al 1984;McConnell 1988). On the other hand, we found a signi®cantly lower _ V O 2max when following the Bruce protocol.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies by Davis et al (1984) and McConnell and Clark (1988) have suggested that the most desirable test protocol for highly trained runners should involve the speed/gradient combination that is similar to what the individual uses during regular training. In this context, it was our hypothesis that the Costill/Fox protocol would yield the highest _ V O 2max among our trained subjects.…”
Section: Discussionmentioning
confidence: 98%
“…The data cover the period from 1980 to 1989. V02m,r was measured [4][5][6] times per year. The highest and lowest values measured during the winter and summer seasons are presented in Table 2-4.…”
mentioning
confidence: 99%
“…ergometer can simulate specific muscle actions during certain activities, the more valid a criterion it becomes [7]. Studies with tethered running using an NMT have provided a very effective way to measure power output, because this method provides a database of strength and velocity [11,21,28].…”
Section: Introductionmentioning
confidence: 99%